The future of social care funding: who pays? ‐ Abstract of the London Discussion. (13th March 2017) - Unknown
Abstract : This abstract relates to the following paper:T. Kenny, J. Barnfield, L. Daly, A. Dunn, D. Passey, B. Rickayzen andA Teow . The future of social care funding: who pays?British Actuarial Journal . doi:10.1017/S135732171600012X